Seismic Fragility of a Single Pillar-Column Under Near and Far Fault Soil Motion with Consideration of Soil-Pile Interaction - Lemsara, Foudhil; Bouzid, Tayeb; Yahiaoui, Djarir; Mamen, Belgacem; Saadi, Mohamed (Engineering, Technology & Applied Science Research, 2023)
The soil-structure interaction is a significant challenge faced by civil engineers due to the complexity potential in terms of seismic fragility evaluation. This paper presents a seismic fragility estimation of a single pier considering seismic ground motion types. Furthermore, sand type, pile diameter, pier height, and mass variation were considered to estimate their effect on the seismic fragility of the concrete pier. Incremental dynamic analysis was performed using a beam on a nonlinear Winkler foundation model. The analysis model condition compared near- and far-ground motion effects. Dynamic analysis and fragility assessment of the single-pier structure showed that low mass center produced less vulnerability of the concrete pier in the two cases of the sand type under near- and far-ground motions. The near and far earthquake simulations at complete failure probability had a difference of less than 5% when 0.65s<T1<1s and 2.4<T1/T2, but the opposite was shown when T1<0.5s and 3<T1/T2 were present together.